Diabetes and Its Complications (IntechOpen, 2018)
Diabetes is a complex, progressive disease, which is accompanied by several complications. It is listed among the most common endocrine disorders and a global metabolic epidemic disease. This book focuses on the recent progress in diabetes research worldwide. It has been written by extensively acknowledged experts, with each chapter providing a unique data on developing features of diabetes. It covers the interactions between diabetes and several disorders. Also, it suggests some treatments for this disease offering us hope in prevention and successful improvement.